Anderson localization in metamaterials and other complex media (Review Article): Оптика и магнитооптика - Gredeskul, Sergey A.; Kivshar, Yuri S.; Asatryan, Ara A.; Bliokh, Konstantin Y.; Bliokh, Yuri P.; Freilikher, Valentin D.; Shadrivov, Ilya V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
We review some recent (mostly ours) results on the Anderson localization of light and electron waves in complex disordered systems, including: (i) left-handed metamaterials, (ii) magnetoactive optical structures, (iii)graphene superlattices, and (iv) nonlinear dielectric media. First, we demonstrate that left-handed metamaterials can significantly suppress localization of light and lead to an anomalously enhanced transmission. This suppression is essential at the long-wavelength limit in the case of normal incidence, at specific angles of oblique incidence(Brewster anomaly), and in the vicinity of the zero-ε or zero-μ frequencies for dispersive metamaterials. Remarkably, in disordered samples comprised of alternating normal and left-handed metamaterials, the reciprocal Lyapunov exponent and reciprocal transmittance increment can differ from each other. Second, we study magnetoactive multilayered structures, which exhibit nonreciprocal localization of light depending on the direction of propagation and on the polarization. At resonant frequencies or realizations, such nonreciprocity results in effectively unidirectional transport of light. Third, we discuss the analogy between the wave propagation throughmultilayered samples with metamaterials and the charge transport in graphene, which enables a simple physicalexplanation of unusual conductive properties of disordered graphene superlatices. We predict disorder-induced resonances of the transmission coefficient at oblique incidence of the Dirac quasiparticles. Finally, we demonstrate that an interplay of nonlinearity and disorder in dielectric media can lead to bistability of individual localized states excited inside the medium at resonant frequencies. This results in nonreciprocity of the wave transmissionand unidirectional transport of light.